Preparation Booklet Based Characteristics Epidermis and Epidermal Derivatives of Purple and White Solanum melongena L. Leaves for SMA Class XI - Salamah, Zuchrotus -; Sasongko, Hadi; Panjaitan, Annisa Hanif (Bioeducation Journal, 2024)
The teaching materials used in the biology learning process in high school are mostly still limited to the use of biology textbooks without additional teaching materials, especially on the material on the structure and function of plant tissues. This study aims to determine the quality of booklets compiled for class XI learning on the structure and function of plant tissue based on the results of research on the characteristics of the epidermis and epidermal derivatives of purple and white eggplant leaves. The development model used in this study is the ADDIE model which is limited to the ADD stage. The data analysis technique used is product assessment data analysis by learning expert using a Likert scale. The results of the booklet assessment by learning experts obtained an average value of 89.16%. Based on the results of this assessment, the booklet on the structure and function of plant tissue is very good to be used for testing as biology teaching material for class XI senior high schools.